BRDF Model of Mars Simulation Soil and Its Comparison with BRDF of Earth Sand. (16th March 2021) - Yang, Yu-Feng; Han, Xiang; Jiang, Ming-Bo; Han, An-Li; Li, Wen-Shuai
Abstract : In this paper, a seven-parameter BRDF model with double-peak characteristic, which could fit double-peak data, was adopted to fit the BRDF of Mars simulation soil. At the same time, the three-dimensional figure of the original data of the sample and the three-dimensional curve of the fitted curve were given. The results proved that the model worked well for this type of data. In addition, the experimental data of four kinds of earth sand samples with different roughness were also fitted and analyzed. It was found that the model still had a good fitting effect on such data. At last, the Mars simulation soil and the four kinds of earth sand samples with different roughness were compared horizontally and vertically. Moreover, the double-peak characteristics and other properties of the Mars simulation soil and the earth sand were analyzed under the same and different roughness.